Examining relationships between customary and state institutions in Ghana's decentralized system - Belden, Cory (International Food Policy Research Institute, 2010)
Traditional authorities are powerful leaders alongside the state in Ghana. The chieftaincy has been resilient to “modernization”—maintaining land rights, allegiance from citizens, and influence in rural communities. Nonetheless, there are few rules defining their official role in the local government structure. It is empirically acknowledged that chiefs seriously impact the development of their communities. Hence, this study looks for factors that might explain the state's deficiency in policy regarding chiefs. This analysis combines the Institutional Analysis and Development (IAD) framework with theory on formal and informal rules. Not only does this adaptation provide additional insight, but it helps to reduce the complexity in political research on dual governance bodies. Findings suggest that the formal and informal rule sets coupled with the resources available to state and customary actors result in strong exchange organizations between the two institutions. Incentives encourage noninterference and avoidance from the state; thus, rules concerning the chieftaincy are rarely enforced or modified. If attempting to harness collaboration and mitigate conflict and collusion, the state—in partnership with the chiefs—might reconsider the lawful role and authorities of the chiefs at local levels. Based on the analysis, policy revisions are needed to improve the outcomes of the institutional arrangement; however, major changes may be difficult to achieve in the current political context.